Real and ideal European maritime transfers along the Atlantic coast during the Neolithic - Serge Cassen; Carlos Rodríguez-Rellán; Ramon Fábregas Valcarce; Valentin Grimaud; Yvan Pailler; Bettina Schulz Paulsson (Documenta Praehistorica, 2019)
The history of research on the Neolithic of the Atlantic façade shows how speculation about prehistoric mobility, especially across the sea, is mainly based on three types of archaeological evidence: megalithic monuments, rare stones, and pottery decoration. With the aim of approaching the issue from other perspectives, we have focused on the Morbihan area, a focal point of the European Neolithic during the mid-5th millennium BC. The analysis of this area has allowed us to grasp which objects, ideas and beliefs may have been desired, adopted and imitated at the time. We shall begin with an architectural concept, the standing stone. These were sometimes engraved with signs that can be directly compared between Brittany, Galicia (NW Spain) and Portugal, but for which there are no intermediate parallels in other areas of the French or Spanish coast. The unique accumulation and transformation of polished blades made of Alpine rocks and found inside tombs or in other sort of depositions in the Carnac region allowed us to establish a second link with Galicia and the Atlantic coast of the Iberian Peninsula, where certain types of the axes were imitated using a set of different rocks (sillimanite, amphibolite). Finally, the variscites and turquoises from different Spanish regions were used for the manufacture of beads and pendants at the Carnacean tombs, without it being possible – once again – to retrieve similar objects in the intermediate areas. The mastery of direct Atlantic sea routes is posed as an explanation for this geographical distribution. But, beyond the information drawn from specific artefacts – whose presence/absence should not be used in excess as an argument to endorse or underrate such movements across the ocean – we will return to a more poetic and universal phenomenon: the spell of the sea. Therefore, we will focus on the depictions of boats on the stelae of Morbihan to open such a debate.